CORRELATION BETWEEN KNOWLEDGE OF COVID-19 AND COMPLIANCE TO HEALTH PROTOCOLS OF UNDERGRADUATE STUDENTS IN YOGYAKARTA DURING PANDEMIC COVID-19 - Soekardi, Rodiyah (LPPM Sekolah Tinggi Ilmu Kesehatan Yogyakarta, 2023)
ABSTRACT Background: According to data from the World Health Organization until February 16, 2021, there were 332,360 new cases, 108,579,352 confirmed cases and 2,396,408 deaths of covid-19 in the world. Indonesia is currently the second ranked country in Southeast Asia with a confirmed number of 1,223. 930 after the State of India with confirmed cases reached 10,916,589. Undergraduate students are role models for the community on health behavior which is related to knowledge. Knowledge is one of the factors that affect a person's compliance. Purpose: The aim of this study was to determine the relationship between knowledge of covid-19 and compliance to the health protocols of undergraduate students Faculty of Science and Technology, Respati Yogyakarta University. Research Methods: This is analytical research with 92 respondents who were taken through purposive sampling technique. The data was collected by a questionnaire and processed in the chi-square test analysis to determine the correlation between the independent variable and the dependent variable. Results: Most of the of respondents were male. Most of respondents have good knowledge about covid-19 and almost all of respondents comply with health protocols Conclusion: Statistically there is correlation between knowledge of covid-19 and compliance to health protocols of undergraduate students the Faculty of Science and Technology, Respati Yogyakarta University, with p-value of 0.036 < 0.05 which means there is a significant correlation between knowledge of covid-19 and compliance to health protocols Keywords: covid-19, knowledge, compliance, health protocol